Discovery of a new Steinernema sp. (Rhabditida: Steinernematidae) with higher shelf life and better efficacy against red palm weevil under laboratory conditions - Anes, K.M.; Babu, Merin; Sivadasan, Jinu; Josephrajkumar, A. (Journal of Plantation Crops, 2020)
Entomopathogenic nematodes (EPN) are excellent bio-control agents for the management of insect pests of soil and cryptic habitat. One of the greatest challenges in the successful utilization of EPN is the poor shelf life of infective juveniles (IJs) under ambient temperature. The present study aimed to evaluate the survival and virulence of different EPN species for determining a superior one in the bio-suppression of red palm weevil (RPW). Among the five species of Steinernematids and two Heterorhabditid isolates evaluated, Steinernema sp. (S0804) sustained up to 13 months, with a desirable survival of 100 per cent during the first five months to about 64 per cent ten months after storage at ambient temperature. Virulence of Steinernema sp. (S0804) sustained up to ten months of storage, was confirmed using Galleria mellonella inoculation test. However, the viable IJs were observed only up to one month in both the Heterorhabditids and up to a period of four to six months of storage in all other Steinernematids. The Steinernema sp. (S0804) was also found to be efficacious against the grubs of RPW in filter paper bio-assay inducing 100 per cent larval mortality in 72 h when applied @ 200 IJs per grub and confirmed further by leaf petiole bioassay. The study thus revealed higher survival and virulence of Steinernema sp. (S0804) and also found to be a potential bio-control agent against RPW. To the best of our knowledge, this is the first EPN isolate reported, which could survive for more than one year at ambient temperature without any additives.